Molecular Study of Childhood Steroid-Resistant Nephrotic Syndrome: A Hospital-Based Study - Singh, Akanksha; Singh, Ankur; Mishra, Om Prakash; Prasad, Rajniti; Narayan, Gopeshwar; Batra, Vineeta V; Tabatabaeifar, Mansoureh; Schaefer, Franz (Journal of Pediatric Genetics, 2021)
Steroid-resistant nephrotic syndrome (SRNS) patients with genetic mutations most commonly have histology of focal segmental glomerulosclerosis (FSGS) and do not respond to immunosuppressive drugs. We report the molecular screening results of 18 pediatric SRNS cases presented to our nephrology clinic. Three pathogenic variants have been detected, two previously reported and one novel variant. The reported pathogenic variants have been detected in NPHS1 and NPHS2 genes. A novel pathogenic variant has been detected in the inverted formin 2 gene (INF2) gene. We did not detect any variant of the WT1 gene. There were 13 males. Mean age of study participants at enrollment was 69 months. There were 12 cases of primary SRNS. The mean duration from onset of symptoms to SRNS diagnosis was 13 months. FSGS and minimal change disease (MCD) were present in the same number of cases. The response rate (complete or partial) to immunosuppressive drugs was seen in only one patient in the genetic SRNS group (n = 3), while the response rate in nongenetic cases (n = 15) was 80%. Two nonresponders in the genetic SRNS group had FSGS for histopathology and pathogenic variants (NPHS2 and INF2). The other three nonresponders in the nongenetic SRNS group had both FSGS (n = 1) and MCD (n = 2) histopathology. There were two deaths in the study cohort of the nongenetic SRNS group. This study highlights the screening of the SRNS cohort by a panel of extended genes rather focussing on the three most common genes (NPHS1, NPHS2, and WT1). This further confirms the molecular etiology of SRNS in three cases and extends the list of pathogenic variants of genetic SRNS in the North Indian population. This is the first study in the eastern part of Uttar Pradesh in India.
Keywords: steroid-resistant nephrotic syndrome; focal segmental glomerulosclerosis; genetic; pediatric